Pengaruh Kenaikan Laju Alir Fluida Panas dan Arah Aliran terhadap Kinerja Plate and Frame Heat Exchanger - Achmad, Feerzet; Naldi, Roy; Uzlifah Janah, Dikri; Sufra, Rifqi; Yuniarti, Reni (Talenta Publisher (Universitas Sumatera Utara), 2024)
Plate and Frame Heat Exchanger (PFHE) is a plate and frame type heat exchanger that is efficient and effective in improving energy efficiency. Research using PFHE aims to determine the effect of increasing the flow rate of hot fluid on heat exchanger performance. This research was conducted at a flow rate variation of 0.7 L/min, 0.9 L/min, 1.1 L/min, 1.3 L/min, 1.5 L/min, 1.7 L/min, and 1.8 L/min with 180 seconds of testing each variation and recording data every 2 seconds. The cold fluid used is tap water and the hot fluid used is distilled water. The results showed that with the increase in hot fluid flow rate, the performance of PFHE also increased because the effectiveness of NTU (Æ-NTU) increased. The Æ-NTU value of unidirectional flow is 25.37% - 44.87% and in the opposite direction 37% - 68.39%. The largest Æ-NTU value in the countercurrent flow indicates that the countercurrent flow is more effective than the unidirectional flow. In addition, increasing the flow rate increases the Reynold's number (Nre) and Nusselt's number (Nu) which indicates the greatest convection heat transfer occurs at the highest flow rate.